Analytical Method Development and Validation by RP-HPLC and UV Spectrophotometric for Estimation of Daprodustat in Bulk and Pharmaceutical Dosage Form - Patil, Pranita Prabhakar; Gagare, Sunita Sunil; Jain, Ashish Suresh (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: This research aimed to systematically boost the development and validation of newly devised, precise, reproducible and accurate UV and Reverse Phase High Performance Liquid Chromatography (RP-HPLC) methods for Daprodustat. Materials and Methods: UV-visible spectrophotometer (Jasco V-730) was used for the analysis and the absorbance was measured across the UV and visible spectra. Measurements were taken at 265 nm, a UV wavelength. Samples were prepared in methanol and selected for compatibility with both UV-vis spectroscopy and the analytes being studied. HPLC-Chromatographic separation was accomplished on a Waters C18 column [150×4.6 mm, 5 μm]. The mobile phase was 0.1% perchloric acid in water: acetonitrile (50:50, V/V), the flow rate was set at 1.0 mL/min and the detector wavelength was 265 nm utilizing the UV detector coupled with an integrator program and data recorder. Results: Daprodustat had a retention time of 15.8 min. With a correlation coefficient of 0.999, the linearity concentration varied from 5-25 μg/mL (HPLC) and 2-10 μg/mL (UV). The accuracy ranged between 98.25%-101.89% (HPLC) and 100.91%-101.40% (UV). In this study, observed that the UV method yielded RSDs with precision less than 2% for both intraday (1.43%) and interday (1.20%) analyses. Similarly, the HPLC method demonstrated system precision (1.56%) and method precision (1.52%) below 2%. Conclusion: Successfully developed and validated the HPLC and UV spectrophotometric techniques in compliance with the specificity, precision, linearity, accuracy, LOD, LOQ and robustness guidelines outlined by the International Council for Harmonization (ICH). Subsequently, the method was applied for routine analysis purposes.
Keywords: Daprodustat; RP-HPLC; UV-Spectroscopy; Validation; Analytical Method